Haemolytic anaemia: a consequence of COVID-19. Issue 12 (10th December 2020) - Jawed, Memoona; Hart, Elizabeth; Saeed, Malik
Abstract : A man in his early 50s presented with jaundice, mild shortness of breath on exertion and dark urine. He had had coryzal symptoms 2 weeks prior to admission. Medical history included obstructive sleep apnoea and hypertension. His initial blood tests showed a mild hyperbilirubinaemia and acute kidney injury stage 1. Chest X-ray and CT pulmonary angiogram were negative for features suggestive of COVID-19. He later developed a drop in haemoglobin and repeat bloods showed markedly raised lactate dehydrogenase and positive direct antiglobulin test. These results were felt to be consistent with a haemolytic anaemia. A nasopharyngeal swab came back positive for COVID-19. We suspect the cause of his symptoms was an autoimmune haemolytic anaemia secondary to COVID-19 which has recently been described in European cohorts.